PROACTIVE PURCHASE BEHAVIOUR AND THEIR RELATIONS IN SIMPLE SATISFACTION MODEL (Polityki Europejskie, Finanse i Marketing)
The purpose of the paper was to verify how proactive shopping behaviours, as declared by the respondents, affect the relationship between expectations, perceived quality and customer satisfaction within a simple satisfaction model. The subject of research was supermarket customers. The authors of the article assumed ten proactive shopping behaviours and then built and verified a satisfaction model in the groups of respondents declaring, or not declaring, the given behaviour. The main conclusions resulting from the analysis is that satisfaction with purchases is more determined by the perceived quality in the case of customers who declare frequent purchases of products that improve the standard of living, consistency in purchasing perceived products and rapidity of purchasing decisions.